New trends in training science: The use of vibrations enhancing performance - Bosco, C.; Cardinale, M.; Tsarpela, O.; Locatelli, E. (1999)
Authors carried out studies to investigate the effects of vibrations on human performance. The first study carried out was conducted to study the effects of whole body vibrations on the mechanical power of the lower limbs. For this aim, fourteen active subjects involved in team sports training voluntarily participated in the experiment. Another study was conducted to observe the behaviour of human skeletal muscle following one session of 10 minutes application of whole body vibration treatment. In this case the subjects were six female elite volleyball players. In another study conducted on 12 national level boxers vibrations had been applied to the upper limbs and it has also been found to produce an enhancement of neuromuscular performance. The hormonal responses to vibrations were studied in handball players who underwent 7 repetitions of 1 min. each of vibrations and a test on vertical jumping performance. In this study, six players of the Italian national team were tested. After reporting about the different studies the scientific basis of vibrations is widely explained. The following conclusion is drawn: The use of vibrations in an athletic setting offers new possibilities to coaching science. Resistance training effectiveness has been demonstrated due to the possibility of enhancing neuromuscular performance, power output. strength and hormonal profile. However. the time needed for these adaptations to occur is relatively long as compared to the possibilities offered by vibration treatments. It should be recognised however, that vibrations need to be viewed not as a substitute tool of resistance exercise. but as a valid additional means to be implemented in a training routine in association with all the other traditional methodologies nowadays utilised. New studies need to be conducted to analyse chronic responses. different treatment protocols and the effects of the association of vibrations with conventional training means for improving the knowledge in this interesting and exciting tool of sports science.